Autism spectrum disorder: psychiatric comorbidities - van Schalkwyk, Gerrit (Henry Stewart Talks, 2020)
Co-occurring symptoms in ASD that are not core features, Anxiety, Obsessive Compulsive Disorder (OCD), Psychotic symptoms, Gender identity, Clinical and conceptual approaches to handle co-occurring symptoms